If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11c = -11 Solving -11c = -11 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-11'. c = 1 Simplifying c = 1
| 2(q-5)+2=16 | | (3x-5)-(6x-1)= | | X=2.25+.75y | | x^2+8x=3x+24 | | 13s+16s-20s=36 | | 8x^5=2x^2m+3 | | -8u+30=-2u | | 8(f-87)-6=66 | | -9(1/2x-3) | | 79g-73g=54 | | 9(t+1)-13=14 | | (X-4)+3(x+5)=51 | | 4(q-13)-6=2 | | -5v-17=9(v-5) | | p*204=342 | | -3/5*-3/5*-3/5*-3/5*-3/5 | | 10-d=4 | | 12b+3b-6b-8b-1=15 | | 7log(3x)+3log(5x)=5 | | 7h-35=95 | | 10s-12s+3s=-6 | | -20a+12a+11a=9 | | 10=3(y+2)+1 | | 10c-7c=18 | | 4z^10+6=1 | | 3(k-7)+2=8 | | 4z+5z=12+42 | | 19z+47=185 | | 2+3z=11 | | -4y+3b+8y+8b= | | 17x+17=4(4x+4) | | P=2a+2l |